Border cities and territorial development: The Portuguese-Spanish case - Medeiros, E.; Neto, P. (Congresso Internacional Globalizações (s)em Fronteiras: heranças e memórias partilhadas na Euroregião Alentejo–Algarve–Andaluzia e Eurocidades, Livro de resumos, 2022)
Portugal and Spain share what is one of the oldest unchanged national borderlines in the World. It has remained practically unchanged for 800 years. As a result, the formal cross-border cooperation process between the two Iberian countries was only engaged, with significant formal partnerships, after the 1990s, following the implementation of the EU INTERREG-A Communitive Initiative. As time progressed, this Initiative, later on transformed into a EU Cohesion Policy goal (European Territorial Cooperation) contributed to an exponential growth of cross-border cooperation processes, translated into the creation of more than 100 cross-border entities across the Portuguese-Spanning border. These included not only Euroregions, and later on European Groupings of Territorial Cooperation (EGTCs), but also several Eurocities close to the border. Indeed, in a context in which the Portuguese-Spanish border region faces, in vast areas, a dramatic depopulation process, the role of border cities is particularly relevant to retain population and economic activities in the border area. As such, this chapter will analyse the border cities in the Portuguese-Spanish border region and their contribution to the territorial development of this border region. A more detailed analysis will be done to the case of the Eurocity Elvas (PT) - Badajoz (ES). In essence, the EUROBEC Eurocity aims to facilitate cross-border cooperation processes in the Alentejo-Extremadura cross-border area which can facilitate the lives of border dwellers and cross-border commuters. For this, it aims, amongst other goals, to improve the sharing of cross-border services, equipment and infrastructure by citizens from each of the three involved municipalities, and to reinforce already established cross-border networks in the border area.